2011
DOI: 10.1007/s00464-011-1593-5
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic transgastric endoscopic retrograde cholangiopancreatography (ERCP) after gastric bypass: case series and a description of technique

Abstract: The findings demonstrate that gastric bypass patients with biliary pain can be successfully evaluated endoscopically by laparoscopic transgastric ERCP for sphincter of Oddi dysfunction. The rate for technical success and complications does not appear to be significantly greater than for standard ERCP. A few helpful techniques were noted during this experience. Comparison of efficacy with that of a prior study was limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(38 citation statements)
references
References 13 publications
1
35
0
2
Order By: Relevance
“…The endoscope is inserted through trochar from the abdominal wall to the gastrostomy opening and then to the biliary tract. This technique was successful in 9 out of 10 patients included in the study by Lopes et al These impressive results were confirmed by Bertin et al, in which successful biliary cannulation was achieved in 94% of 21 RYGBP patients who underwent laparoscopic assisted ERCP [50]. In conclusion, bariatric surgeries are increasing due to the obesity epidemic.…”
Section: Endoscopy In the Treatment Of Bariatric Surgery Complicationsmentioning
confidence: 76%
“…The endoscope is inserted through trochar from the abdominal wall to the gastrostomy opening and then to the biliary tract. This technique was successful in 9 out of 10 patients included in the study by Lopes et al These impressive results were confirmed by Bertin et al, in which successful biliary cannulation was achieved in 94% of 21 RYGBP patients who underwent laparoscopic assisted ERCP [50]. In conclusion, bariatric surgeries are increasing due to the obesity epidemic.…”
Section: Endoscopy In the Treatment Of Bariatric Surgery Complicationsmentioning
confidence: 76%
“…Case series described in the literature point to success rates up to 100.0%, with complication rates similar to the traditional procedure [10,[43][44][45][46][47], demonstrating that it is technically superior to those using long frontal vision devices.…”
Section: Discussionmentioning
confidence: 99%
“…2017;7(4):58-63 the surgical team throughout the procedure are important factors that limit the diffusion of the use of this technique [10,[43][44][45][46][47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While cost is a significant disadvantage, surgery would still be the first choice in community hospitals where there are limited facilities for balloon endoscopy or where there is time and skill constraints. Furthermore, sometimes the previous operative report of the RYGB surgery might not detail the technique used, post-operative complication or the anatomy and length of the roux as well as pancreatico-biliary limb [7][8][9][10]. The disadvantages of surgery-assisted ERCP are that it involves surgery and that it may take time for the surgeon to identify the gastric remnant due to the altered anatomy from previous surgery in these patients [11][12][13].…”
Section: Introductionmentioning
confidence: 99%